Perancangan Mainan Jengga Modifikasi untuk Melatih Diskusi Kelompok Siswa Kelas XI SMA - R, Hani; Insani, Handayani Madania; Hafiyan, R. Moch. Rizal; Jayanti, Ghia Tri (Fakultas Industri Kreatif Universitas Surabaya, 2026)
21st-century learning, especially the skills that are crucial in the era of the Fourth Industrial Revolution, is very important to develop, one of which is through discussion. However, the implementation of discussion dominated by presentations is often monotonous and focuses only on results, not the process. This encourages students to simply copy and read, indicating that the development of 21st-century skills is not yet optimal. To address this issue, this study proposes a modified version of the Jenga game designed to facilitate student discussions on flood mitigation and make learning more enjoyable. This design applies the SCAMPER method, specifically the aspects of Substitute, Adapt, Modify, Put to other uses, and Combine. The results of the study show that this modified Jenga successfully accommodates small group discussions among students, allowing teachers to directly monitor their performance. Additionally, this game makes learning more enjoyable, especially with the “steal your opponent's block” rule, which increases student interaction and enthusiasm.